Endocannabinoid 2-Arachidonoylglycerol Self-Administration by Sprague-Dawley Rats and Stimulation of in vivo Dopamine Transmission in the Nucleus Accumbens Shell - De Luca, Maria Antonietta; Valentini, Valentina; Bimpisidis, Zisis; Cacciapaglia, Fabio; Caboni, Pierluigi; Di Chiara, Gaetano (Frontiers in Psychiatry, 2014)
2-Arachidonoylglycerol (2-AG) is the most potent endogenous ligand of brain cannabinoid CB1 receptors and is synthesized on demand from 2-arachidonate-containing phosphoinositides by the action of diacyglycerol lipase in response to increased intracellular calcium. Several studies indicate that the endocannabinoid (eCB) system is involved in the mechanism of reward and that diverse drugs of abuse increase brain eCB levels. In addition, eCB are self-administered (SA) by squirrel monkeys, and anandamide increases nucleus accumbens (NAc) shell dopamine (DA) in rats. To date, there is no evidence on the reinforcing effects of 2-AG and its effects on DA transmission in rodents. In order to fill this gap, we studied intravenous 2-AG SA and monitored the effect of 2-AG on extracellular DA in the NAc shell and core via microdialysis in male Sprague-Dawley rats. Rats were implanted with jugular catheters and trained to self-administer 2-AG (25g/kg/inf iv) in single daily 1h sessions for 5 weeks under initial Fixed Ratio (FR) 1 schedule. The ratio was subsequently increased to FR2. Active nose-poking increased from the 6th SA session (acquisition phase) but no significant increase of nose-pokes was observed after FR2. When 2-AG was substituted for vehicle (25th SA session, extinction phase), rate responding, as well as number of injections, slowly decreased. When vehicle was replaced with 2-AG, SA behavior immediately recovered (reacquisition phase). The reinforcing effects of 2-AG in SA behavior were fully blocked by the CB1 receptor inverse agonist/antagonist rimonabant (1 mg/kg ip, 30 min before SA session). In the microdialysis studies, we observed that 2-AG (0.1-1.0 mg/kg iv) preferentially stimulates NAc shell as compared to the NAc core. NAc shell DA increased by about 25% over basal value at the highest doses tested (0.5 and 1.0 mg/kg iv). The results obtained suggest that the eCB system, via 2-AG, plays an important role in reward.